2010
DOI: 10.1258/jicp.2009.009018
|View full text |Cite
|
Sign up to set email alerts
|

Critical pathway for patients undergoing aortic-surgery: Impact on postoperative care at an intensive care unit in Sweden

Abstract: Background: In January 2007, the intensive care unit (ICU) at a Swedish hospital introduced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The nurses' views were that the CP led to a more efficient rehabilitation for the patient, which is consistent with findings from a retrospective review of patient records performed at the same ICU by Lyckner et al (2010). Another conception that emerged was that the CP is a reference guide for understanding a standard course of postoperative recovery.…”
Section: Quality Of Caresupporting
confidence: 65%
See 1 more Smart Citation
“…The nurses' views were that the CP led to a more efficient rehabilitation for the patient, which is consistent with findings from a retrospective review of patient records performed at the same ICU by Lyckner et al (2010). Another conception that emerged was that the CP is a reference guide for understanding a standard course of postoperative recovery.…”
Section: Quality Of Caresupporting
confidence: 65%
“…A previously conducted study in the same setting showed that postoperative actions, e.g. removal of the nasogastric tube and intake of oral nutrition, which are assumed to result in more effective rehabilitation, were performed earlier in the postoperative course after the implementation of the CP (Lyckner et al 2010). This finding is consistent with studies of CP implementation in other settings (Barker et al 1999;Murphy et al 2007;Ronellenfitsch et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…The daily care of critically ill patients at intensive care units (ICUs) is complex, requiring integrated skills from numerous different specialties, and teamwork is crucial for optimal outcome . In this context, protocol‐based care can provide a useful support to healthcare professionals, facilitate evidence‐based practice, improve patient care, reduce time with mechanical ventilation, decrease length of stay and imply cost savings . However, because the development and use of care protocols differ between settings and countries, there is a need for international knowledge sharing with regard to development, implementation and evaluation of the phenomenon .…”
Section: Introductionmentioning
confidence: 99%
“…According to our CP plan, we removed the nasogastric (NG) tube as soon as the patients were extubated. Patients undergoing CABG have indicated that the early removal of nasogastric feeding tube had a positive effect on early postoperative feeding (Lyckner et al., ). The early removal of the nasogastric feeding tube also improves the nutrition and mobilisation levels of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving care guided by a CP have been shown begin to eat and drink earlier, and recover earlier (Lyckner et al., ; Saar et al., ). One of the main aims of the CP was to begin normal feeding.…”
Section: Discussionmentioning
confidence: 99%